1983
DOI: 10.1071/ch9831873
|View full text |Cite
|
Sign up to set email alerts
|

Photoreduction of deazaflavin. Spectroscopic investigations

Abstract: Photophysical and photochemical properties of deazaflavin (3,10-dimethylpyrimido[4,5-b]quinoline- 2,4-(3H,10H)-dione) and some of its 1,5-dihydro derivatives have been investigated. Contrary to earlier reports the photodimer of deazaflavin is non-luminescent throughout the temperature range 77-295 K. Excitation of deazaflavin in the presence of oxalate anion (acetate buffer pH 5.0) causes photodimerization with quantum efficiencies exceeding unity. A mechanism involving a triplet excimer of deazaflavin has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…While NADH-reduced dRf gave only one product (H 2 dRf, as confirmed by its characteristic UV spectrum, Fig. S4.1) [56] EDTA-reduction of dRf yielded H 2 dRf and another product (most likely assigned to the dimeric, half-reduced semiquinone product) appearing simultaneously over time (Fig. S4.2).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…While NADH-reduced dRf gave only one product (H 2 dRf, as confirmed by its characteristic UV spectrum, Fig. S4.1) [56] EDTA-reduction of dRf yielded H 2 dRf and another product (most likely assigned to the dimeric, half-reduced semiquinone product) appearing simultaneously over time (Fig. S4.2).…”
Section: Resultsmentioning
confidence: 75%
“…Already in the 1970s, deazaflavins have been subject of extensive research efforts. Especially Massey, Hemmerich and coworkers have worked out the reactivity of deazaflavins revealing that the deazasemiquinone radical is significantly less stable compared to the 'normal' semiquinone [53][54][55][56][57][58][59][60]. This favours disproportionation and dimerization reactions leading to non-radical products exhibiting low(er) O 2 reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported (Massey and Hemmerich, 1978;Duchstein et al, 1979;Goldberg et al, 1981;Bliese et al, 1983) that prolonged illumination of 3-methyl-5-deazaflavin l h and 3,7,8-trimethyl-5deazaflavin lj in the presence of the electron donor oxalate or EDTA leads to the formation of dimeric compounds 2h, 2j as final products of the photoreduction (Scheme 1). In our work we found that the photoreduction of dFloxs is strongly influenced by the substituent at position 8 and the electron donor used (Link et al, 1986b).…”
Section: Photoreduction Of 5-deazaflavinsmentioning
confidence: 97%
“…6. Here, the energy of the deazaflavin triplet, P Fe À 3 F*, E 0À0 = 2.58, was assumed to be equal to that of 3,10-dimethyl-5-deazaflavin [23] and that of the porphyrin triplet, 3 P Fe * À F, equal to that of tetraarylporphyrinatometals, E 0À0 = 1.50 [24].…”
Section: Cmentioning
confidence: 99%